Juvenile male rats form preferences based on strain when playing in groups but not in pairs - Ham, Jackson R.; Jaiswal, Diya; Waner-Mariquito, Renata; Pellis, Sergio M.; Achterberg, E. J. Marijke (Frontiers in Behavioral Neuroscience, 2025)
Like many young mammals, juvenile rats engage in rough-and-tumble play. Play occurs naturally both in wild and laboratory rats, making it a suitable, ethologically relevant behavior to investigate. In the laboratory, rats are typically housed and tested in dyads, despite living in large colonies in the wild. Consequently, when tested in the lab, rats do not have a choice of partners and are instead paired with whomever the researcher selects. Given that both the amount and style of play rats engage in varies considerably depending on the strain of rat being studied, we tested whether rats select play partners based on strain. To do so, juvenile male Long Evans (LE) focal rats (n = 8) were subjected to three play contexts: (1) group play; (2) dyadic play; and (3) social conditioned place preference. During group play, the LE subject rats were given the choice to play with an LE, a Sprague Dawley (SD), or Fischer 344 rat (F344), simultaneously. During dyadic play, focal rats played one-on-one with an LE, SD, or F344 partner. Finally, the rats were conditioned to a context and a social stimulus, with the context either being paired with an LE (preferred stimulus) or F344 (unpreferred stimulus) partner. We found that, when given a choice in a group setting, LE focal rats prefer to play with same-strain partners over both SD and F344 partners. However, when playing under dyadic conditions (i.e., with an assigned partner), LE rats played with each strain equally. Finally, in the socially conditioned place preference test, we found that the focal rats formed preferences for a particular enclosure, but not for the strain. Together, these results suggest that when given a choice, LE rats prefer to play with their own strain, but when they do not have a choice, any strain will do. Given that the testing paradigm can greatly influence the results obtained and the conclusions drawn, our findings highlight the need to consider the research question(s) being asked when determining the most appropriate paradigms to employ.